High Temperature Die Attach: Study and Power Cycling of Direct-Bonded Silver Joints - Häußler, Felix; Sippel, Marcel; Sprenger, Mario; Liu, Lu; Muckelbauer, Martin; Franke, Jörg (2022 IEEE 9th Electronics System-Integration Technology Conference (ESTC), 2022)
Silver direct bonding as die-attach method is a new approach to form metallurgical bonds between dies and copper-ceramic substrates. Silver as a mono-metallic joining partner is a prerequisite and joined by applying pressure and heat for a given time. The aim of this work is to compare electroless and electroplated silver metallization of copper ceramic substrates applicability for direct bonding. This is achieved by comparing shear strength and durability in active power cycling of the formed joints. For the active power cycling the direct bonded samples are compared to sintered interconnects in the same setup. Results show, that the electroplated metallization performs mechanically slightly more stable than the electroless ones but is significantly influenced by surface roughness. The active power cycling results yield the highest reliability for silver sintered bonds in the raw data after power cycling and for the electroplated joints if a junction temperature correction is applied. The reliable electroplated samples reached the failure criteria at a comparable average number of power cycles as the sintered reference samples. Both groups exhibit bond wire lift-off on the topside interconnect as failure cause. Electroless plating reached less than 10,000 cycles in average compared to 35,000 cycles for sintered and 27,000 cycles for electroplated diodes.<br